The power of starting something stupid : how to crush fear, make dreams happen, and live without regret - Norton, Richie; Norton, Natalie (Shadow Mountain, 2013)
Presents advice on how to defy conventional wisdom and become successful through implementing original business ideas that are based on personal values.